Pengaruh Kinerja Keuangan Terhadap Harga Saham PT Bank Negara Indonesia Tbk Yang Terdaftar di Bursa Efek Indonesia - Harisda; Mardatillah; Batara, Andi Alfian; Amalia, Putri (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2024)
The capital market is a place where businesses get capital from investors. Investors buy shares with the aim of obtaining dividends from the difference between the purchase price and the selling price. The share price is the price per share of a company on the stock exchange. The purpose of this study was to determine the effect of financial performance on the price of BNI shares listed on the Indonesian Stock Exchange for the period 2020-2023. This quantitative study was tested using multiple linear regression using SPSS 26. The results of this study indicate that ROA has a positive effect because the higher the rate of return, the more investors are interested in buying shares which will affect the share price, ROE has a negative effect. The higher the Return On Equity value owned by the company, the lower the company's share price.